Prenatal diagnosis of torcular Herophili thrombosis - Torres-Cepeda, Duly (2021)
Torcular herophili thrombosis is a rare disease of unknown etiology. So far about 50 cases have been described in the literature. Ultrasound is an effective diagnostic method and is useful for follow-up. Characteristic sonographic findings include a well-defined triangular anechoic lesion in the occipital region with an echogenic structure within it which is the thrombus. Doppler ultrasound can help to establish the diagnosis more accurately. The prognosis is variable, as most cases have an irrelevant clinical course due to spontaneous resolution of the thrombus, while other cases may experience cerebral atrophy and death. A case of prenatal diagnosis of torcular herophili thrombosis is presented.